Ring-stage growth arrest: Metabolic basis of artemisinin tolerance in Plasmodium falciparum - Xinyu Yu; Changhong Wang; Yuemeng Zhao; Jianxia Tang; Meng Zhu; Lucien Platon; Richard Culleton; Guoding Zhu; Didier Ménard; Qingfeng Zhang; Jun Cao (iScience, 2023)
Summary: The emergence and spread of artemisinin-tolerant malaria parasites threatens malaria control programmes worldwide. Mutations in the propeller domain of the Kelch13 protein confer Plasmodium falciparum artemisinin resistance (ART-R). ART-R is linked to the reduced susceptibility of temporary growth-arrested ring-stage parasites, but the metabolic mechanisms remain elusive. We generated two PfKelch13 mutant lines via CRISPR-Cas9 gene editing which displayed a reduced susceptibility accompanied by an extended ring stage. The metabolome of ART-induced ring-stage growth arrest parasites carrying PfKelch13 mutations showed significant alterations in the tricarboxylic acid (TCA) cycle, glycolysis, and amino acids metabolism, pointing to altered energy and porphyrin metabolism with metabolic plasticity. The critical role of these pathways was further confirmed by altering metabolic flow or through chemical inhibition. Our findings uncover that the growth arrestment associated with ART-R is potentially attributed to the adaptative metabolic plasticity, indicating that the defined metabolic remodeling turns out to be the trigger for ART-R.